2020
DOI: 10.1038/s41467-020-15289-7
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 dependent phosphorylation of hTERT contributes to cancer progression

Abstract: The telomerase reverse transcriptase is upregulated in the majority of human cancers and contributes directly to cell transformation. Here we report that hTERT is phosphorylated at threonine 249 during mitosis by the serine/threonine kinase CDK1. Clinicopathological analyses reveal that phosphorylation of hTERT at threonine 249 occurs more frequently in aggressive cancers. Using CRISPR/Cas9 genome editing, we introduce substitution mutations at threonine 249 in the endogenous hTERT locus and find that phosphor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 86 publications
(122 reference statements)
0
59
0
Order By: Relevance
“…More recently, 3‐D structural analyses have confirmed that hTERT has the characteristic right‐handed architecture similar to RdRPs found in RNA viruses 8‐10 . We have recently reported that hTERT possesses RdRP activity that is essential for tumorigenesis, 11,12 suggesting that RNA virus and cancer share a similar survival strategy of RNA‐dependent RNA synthesis. Since the 1970s, cancer research has advanced along with research about oncogenic RNA viruses such as Rous sarcoma virus, resulting in the identification of various cellular oncogenes.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…More recently, 3‐D structural analyses have confirmed that hTERT has the characteristic right‐handed architecture similar to RdRPs found in RNA viruses 8‐10 . We have recently reported that hTERT possesses RdRP activity that is essential for tumorigenesis, 11,12 suggesting that RNA virus and cancer share a similar survival strategy of RNA‐dependent RNA synthesis. Since the 1970s, cancer research has advanced along with research about oncogenic RNA viruses such as Rous sarcoma virus, resulting in the identification of various cellular oncogenes.…”
Section: Introductionmentioning
confidence: 73%
“…The structure of hTERT is similar to the characteristic right‐handed architecture of RNA virus RdRPs 6,8,9 . In addition, the inhibition of RdRP activity in hTERT by a genetic approach suppressed the growth of cancer cell lines, 12 suggesting that efforts to search for inhibitors against RdRP activity in hTERT are, in our opinion, a promising strategy for finding candidate anticancer drugs. Thus, we hypothesized that inhibitors against viral RdRPs would also inhibit the RdRP activity in hTERT.…”
Section: Rna‐dependent Rna Polymerase Inhibitorsmentioning
confidence: 86%
See 2 more Smart Citations
“…7 TERT has an RNA-dependent RNA polymerase activity, which is also implicated for cancer progression. 8 TERT expression is mediated by various transcription factors, including MYC, SP-1, E2F, and AP1.…”
Section: Telomerase Confers Cell Immortality a Hallmark Of Cancermentioning
confidence: 99%